CT, MRI, and PET/CT imaging features of thoracic spine epithelioid hemangioma: a retrospective observational study - Hu, Xianwen; Li, Xiaotian; Xiong, Zujiang; Li, Dandan; Cai, Jiong; Wang, Pan (Frontiers in Oncology, 2024)
Introduction Epithelioid hemangioma (EH) is an intermediate locally aggressive tumor that consists of epithelioid cells and endothelial cell differentiation, which can occur at any age, but is most common between the ages of 30 and 40. EH in the thoracic spine is rare, and accurate diagnosis is critical to treatment planning.Our aim was to explore the imaging and clinical data of thoracic spine EH in order to improve the understanding of this rare disease.From January 1, 2018 to June 30, 2023, a database of thoracic spine masses was retrospectively reviewed. Five patients with histologically proven to be thoracic spine EH and complete imaging available were identified and analyzed. Computed tomography (CT) and magnetic resonance imaging (MRI) findings were evaluated separately by two radiologists with more than 10 years experience. Positron emission tomography (PET)/CT were conducted by two nuclear medicine diagnostics with at least 5 years of experience.Results: Patients included 3 male and 2 female patients aged 23 to 56 years (mean age was 38.4±14.3 years).All patients underwent CT, MRI and 18 F-FDG PET/CT examination before treatment. Four patients were limited to one vertebral involvement, only one patient had multiple vertebral involvement, and all tumors involved the accessories, including one involving the posterior ribs. The maximum diameter of the tumor ranges from 2.7 to 4.3.Conclusions: CT,MRI and 18 F-FDG PET/CT findings of thoracic spine EH have certain characteristics, and understanding these imaging findings will help to obtain accurate diagnosis before surgery.